Study on the soil microbial community structure of the Rhizosphere of Camellia sinensis L. in Anping Village, Kaiyang County, Guizhou Province - Jinmei Guo; Jianfeng Li; Shuqing Zhang; Ping Chen (Annals of Microbiology, 2023)
Abstract Background To determine the differences in the microbial communities in the Camellia sinensis L. hairy root, lateral root, and main root rhizospheres in Anping Village, Kaiyang County, Guizhou Province, the community structure, diversity, and main dominant species of bacteria and fungi in different parts of the soil were analyzed by ITS and 16S sequencing. Results In the rhizosphere soil of the main root, lateral root, and hairy root of Camellia sinensis L., there were significant differences in the diversity and richness of the bacterial and fungal communities. The bacterial diversity was the highest and the fungal richness was the lowest in the rhizosphere soil of the main root. In the bacterial community, Proteobacteria, Actinobacteria, Acidobacteria, Chloroflexi, and Gemmatimonadetes were the common dominant bacteria. Rhodospirillaceae, Bradyrhizobiaceae, Hyphomicrobiaceae, Solibacteraceae, and Koribacteraceae were the common dominant bacteria in the rhizosphere soil of different parts of the root system, but the relative abundance of bacteria in different parts of the rhizosphere soil varied greatly. The dominant groups of fungal communities in different parts of the rhizosphere soil were Basidiomycota, Ascomycota, Mortierellomycota, and Sebacinaceae. The structure of the fungal community is similar in different parts. Conclusions Compared with the different parts of the hairy root, lateral root, and main root of rhizosphere soil of Camellia sinensis L. in Anping village, it was found that the abundance of fungal community decreased with the increase of bacterial community abundance, and there were significant differences in bacterial community diversity and structure. However, the fungal community maintained stability among different parts.